2010
DOI: 10.1007/s11162-010-9184-1
|View full text |Cite
|
Sign up to set email alerts
|

Are You Satisfied? PhD Education and Faculty Taste for Prestige: Limits of the Prestige Value System

Abstract: This paper empirically evaluates Caplow and McGee's (The academic marketplace, 1958) model of academia as a prestige value system (PVS) by testing several hypotheses about the relationship between prestige of faculty appointment and job satisfaction. Using logistic regression models to predict satisfaction with several job domains in a sample of more than 1,000 recent social science PhD graduates who hold tenure-track or tenured faculty positions, we find that the relationship between prestige of faculty appoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…One study found institutional image and reputation to be correlated with persistence among business school students (Nguyen and LeBlanc 2001 ) while another found a relationship between prestige of faculty appointment and job satisfaction. This particular study suggested that graduates of highly prestigious PhD programs were most likely to value prestige while graduates of low prestige programs valued salary more highly (Morrison et al 2011 ).…”
Section: Institutional Image and Reputationmentioning
confidence: 77%
“…One study found institutional image and reputation to be correlated with persistence among business school students (Nguyen and LeBlanc 2001 ) while another found a relationship between prestige of faculty appointment and job satisfaction. This particular study suggested that graduates of highly prestigious PhD programs were most likely to value prestige while graduates of low prestige programs valued salary more highly (Morrison et al 2011 ).…”
Section: Institutional Image and Reputationmentioning
confidence: 77%
“…While Rivera's (2012) study focused on hiring dynamics within professional service firms, in the academic context cultural matching may be based on institutional prestige. For example, graduates from prestigious American institutions are often drawn to work in similar environments, resulting in their disproportionate employment at other top schools (Morrison et al 2011). Over time, such status-based homophily can reinforce the collective culture of departments, as well as processes of social closure in the exchange network by creating a "small world" problem in which elite schools share each other's graduates (Clauset et al 2015;Oprisko 2012).…”
Section: Prestige Hierarchies In Academiamentioning
confidence: 99%
“…Faculty who graduated from more prestigious doctoral programs tend to view their programs through a lens of prestige and are unsatisfied if the standards for students, time for research, and other resources of their doctoral program do not match their new institution's conditions (Morrison, Rudd, Picciano, & Nerad, 2011). Also, tenure track faculty bring their social identities (such as gender, race, sexual orientation) to their early career experiences, especially on the tenure track, and operate in specific cultures and disciplines.…”
Section: Theoretical Frameworkmentioning
confidence: 99%